"Napoję cię winem korzennym, moszczem z granatów" (Pnp 8,2b). Pragnienie Oblubieńca w świetle starożytnych i średniowiecznych komentarzy do Pieśni nad Pieśniami - Bardski, Krzysztof (Verbum Vitae, 2004)
In the tradition of the allegorical interpretation of the Song of Songs the Bridegroom of the Song of Songs represents Christ, meanwhile the bride represents the Church. The verse 8,2 shows us the Bride satiating the thirst of the Bridegroom. In the article we tried to analyze and reflect on the commentaries of the Fathers of the Church and medieval writers to this verse in connection with the charisma of Mother Teresa and the Missionaries of Charity centered on the mystery of Jesus' "I thirst" on the cross. The main streams ofthe Christian tradition interpreted the spiced vine in connection with the love of God and the juice of pomegranates in connection with martyrdom.